Seismic Network in Greenland Monitors Earth and Ice System. Issue 2 (14th January 2014) - Clinton, John F.; Nettles, Meredith; Walter, Fabian; Anderson, Kent; Dahl‐Jensen, Trine; Giardini, Domenico; Govoni, Aladino; Hanka, Winfried; Lasocki, Stanislaw; Lee, Won Sang; McCormack, David; Mykkeltveit, Svein; et al.
<x xml:space="preserve">Abstract</x> Some of the most dramatic effects of climate change have been observed in the Earth's polar regions. In Greenland, ice loss from the Greenland ice sheet has accelerated in recent years [Shepherd et al., 2012]. Outlet glaciers are changing their behavior rapidly, with many thinning, retreating, and accelerating [Joughin et al., 2004]. The loss of ice weighing on the crust and mantle below has allowed both to rebound, resulting in high rock uplift rates [Bevis et al., 2012]. Changes in ice cover and meltwater production influence sea level and climate feedbacks; they are expected to contribute to increasing vulnerability to geohazards such as landslides, flooding, and extreme weather.